2010
DOI: 10.1016/j.jasms.2010.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase acid-base properties of melamine and cyanuric acid

Abstract: The thermochemical properties of melamine and cyanuric acid were characterized using mass spectrometry measurements along with computational studies. A triple-quadrupole mass spectrometer was employed with the application of the extended Cooks kinetic method. The proton affinity (PA), gas-phase basicity (GB), and protonation entropy (⌬ p S) of melamine were determined to be 226.2 Ϯ 2.0 kcal/mol, 218.4 Ϯ 2.0 kcal/mol, and 26.2 Ϯ 2.0 cal/mol K, respectively. The deprotonation enthalpy (⌬ acid H), gas-phase acidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…Although not depicted, a hydrogen migration from the oxygen to the nitrogen in the Meisenheimer complex similar to those seen by Mukherjee and Ren [61], produces a stable keto-like ring opened structure (−40.2 kcal mol -1 ). The barrier to this process lays 7.3 kcal mol -1 below the total energy of reactants and may be the pathway that leads to the observed fragmentation products.…”
Section: Potential Energy Surface Of 135-triazine Reactionsmentioning
confidence: 54%
“…Although not depicted, a hydrogen migration from the oxygen to the nitrogen in the Meisenheimer complex similar to those seen by Mukherjee and Ren [61], produces a stable keto-like ring opened structure (−40.2 kcal mol -1 ). The barrier to this process lays 7.3 kcal mol -1 below the total energy of reactants and may be the pathway that leads to the observed fragmentation products.…”
Section: Potential Energy Surface Of 135-triazine Reactionsmentioning
confidence: 54%
“…In principle, melamine can exist in different tautomers (Fig. (C)) . Comparing both tautomeric forms, the structure with − NH 2 groups is more stable .…”
Section: Resultsmentioning
confidence: 99%
“…These complexes are very promising light-emitting materials because of their good thermal stability [5]. The thermochemical properties of cyanuric acid were characterized using mass spectrometry measurements along with computational studies was already reported by Mukherjee and Ren [6]. Cyanuric acid is a triazine derivative and may also be described as two structural isomers, the enol-like triazine-triol and the keto-like tautomer.…”
Section: Introductionmentioning
confidence: 98%